2021
DOI: 10.7554/elife.70931
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and compensation in a bacterial gene regulatory network evolving under antibiotic selection

Abstract: Gene regulatory networks allow organisms to generate coordinated responses to environmental challenges. In bacteria, regulatory networks are re-wired and re-purposed during evolution, though the relationship between selection pressures and evolutionary change is poorly understood. In this study, we discover that the early evolutionary response of Escherichia coli to the antibiotic trimethoprim involves derepression of PhoPQ signaling, an Mg2+-sensitive two-component system, by inactivation of the MgrB feedback… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 102 publications
4
54
0
Order By: Relevance
“…In antibiotic stress conditions, alterations in gene expression in genes involved in surface structures, re ux systems, and enzymes linked to antibiotic inactivation, have been observed. The regulation of these genes are usually under control of bacterial sensory systems (10,24). A substantial increase in the expression of the virF of Shigella and EIEC was seen in response to cipro oxacin Sub-MICs in our study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In antibiotic stress conditions, alterations in gene expression in genes involved in surface structures, re ux systems, and enzymes linked to antibiotic inactivation, have been observed. The regulation of these genes are usually under control of bacterial sensory systems (10,24). A substantial increase in the expression of the virF of Shigella and EIEC was seen in response to cipro oxacin Sub-MICs in our study.…”
Section: Discussionsupporting
confidence: 55%
“…In some bacteria, similar responses to other environmental stresses such as antimicrobial pressure have been shown (10,11).…”
Section: Introductionmentioning
confidence: 83%
“…These have a dual effect, both hyperactivating the NtrB kinase, and strongly upregulating ntrBC expression through their positive autoregulatory loop. Mutational loss of a negative repressor leading to overactivity and overexpression of a positively autoregulated transcription factor has also been observed to drive adaptation in several experimental and clinical settings 35,64,65 . In contrast, we have identified that to achieve the same effect of high activity and high expression in PFLU1131/2, multiple mutations were required.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, activation of two component regulatory systems linked to e ux pumps such as PhoPQ, PmrA, in response to therapeutics were proposed to mediate drug resistance in many bacteria [32,33]. Two component regulatory systems are activated in the response of environmental stimuli [34]. In vivo, environment is complex and can vary from patient to patient depending upon the disease status, co morbidity and use of other drugs.…”
Section: Discussionmentioning
confidence: 99%